Modeling dynamic stall on wind turbine blades under rotationally augmented flow fields. Issue 3 (9th March 2015) - Guntur, Srinivas; Sørensen, Niels N.; Schreck, Scott; Bergami, Leonardo
Abstract: This paper presents an investigation of two well‐known aerodynamic phenomena, rotational augmentation and dynamic stall, together in the inboard parts of wind turbine blades. This analysis is carried out using the following: (1) the National Renewable Energy Laboratory's Unsteady Aerodynamics Experiment Phase VI experimental data, including constant as well as continuously pitching blade conditions during axial operation; (2) data from unsteady delayed detached eddy simulations (DDES) carried out using the Technical University of Denmark's in‐house flow solver Ellipsys3D; and (3) data from a reduced order dynamic stall model that uses rotationally augmented steady‐state polars obtained from steady Phase VI experimental sequences, instead of the traditional two‐dimensional, non‐rotating data. The aim of this work is twofold. First, the blade loads estimated by the DDES simulations are compared with three select cases of the N‐sequence experimental data, which serves as a validation of the DDES method. Results show reasonable agreement between the two data in two out of three cases studied. Second, the dynamic time series of the lift and the moment polars obtained from the experiments are compared with those from the dynamic stall model. This allowed the differences between the stall phenomenon on the inboard parts of harmonically pitching blades on a rotating wind turbine and the classic dynamic stall representation in two‐dimensional flow to be investigated. Results indicated a good qualitative agreement between the model and the experimental data in many cases, which suggests that the current two‐dimensional dynamic stall model as used in blade element momentum‐based aeroelastic codes may provide a reasonably accurate representation of three‐dimensional rotor aerodynamics when used in combination with a robust rotational augmentation model. Copyright © 2015 John Wiley & Sons, Ltd.